Monte carlo simulation of ferromagnetic hysteresis of 3 dimensional ising spins using random walk under lennard-jones potentials - Reungyos J. (2014)
This work aims to investigate the evolution of magnetic behavior under the effect of external magnetic field applied on the itinerant magnetic Ising spins (or the Ising fluid). Monte Carlo and Random Walk methods were used to simulate the Ising spins in a 3-dimensional space, and to examine the dynamic hysteresis properties. Metropolis algorithm was introduced to update spin configurations on the continuous space. By applying an external magnetic field to Ising spins interaction via Lennard-Jones potential, we found a) at the low temperature and frequency ranges the hysteresis loops was ferromagnetic, broad shaped and expanded, and b) at the high temperature range, the hysteresis loop was paramagnetic and reduced. It is proven that properties of the hysteresis of ferro-fluid can be controlled by varying temperature and frequency of theirs magnetic field signals. Hence, this work may be beneficial to the biomedical engineering applications such as cancer therapy. Copyright © Taylor &Francis Group, LLC.